Membuat Tabel dan Dokumen Banyak Kolom dalam Microsoft Word - Algita Algita; Alia Patawaran; Aprillya Paskah Kritiani Mona; Chelzy Juliastri; Elan Estetika Telaumbanua; Ebi Denis Prianto; Enjelika Enjelika; Ivan Permadani; Perawati Sasambe; Justicia F.S Kalangi; Selpina Djamdjik; Valentina Daad (STIKes Ibnu Sina Ajibarang, 2024)
Microsoft Word is word processing software that is widely used to create text documents. The table creation and column arrangement features in Microsoft Word are very useful in presenting structured data and preparing text layouts that are easier to read. Tables are used to display data in the form of rows and columns, making it easier to compare, group and organize information that requires a neat and structured format. Meanwhile, the column feature in Microsoft Word allows dividing text vertically, which is often used in documents with article, bulletin or newspaper formats, thereby increasing document readability.This writing examines the basics of using tables and columns, from how to create them to setting column widths, spacing between columns, and using various layout formats in tables. Apart from that, table integration techniques in multi-column documents and vice versa are also discussed, to increase the effectiveness of conveying information. This study aims to help users make optimal use of these features, with an approach based on the principles of information design and text readability. By understanding and mastering this technique, users are expected to be able to produce documents that are more professional, informative and aesthetic.